Pengaruh Model Pembelajaran Predict-Observe-Explain (POE) Berbantuan Simulasi Virtual Terhadap Penguasaan Konsep Fisika Siswa SMA - Nurbaiti Nurbaiti; Kosim Kosim; Muhammad Taufik (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2020)
This study aims to determine the effect of Predict-Observe-Explain (POE) learning models assisted by virtual simulations on the mastery of physics concepts in high school students. This type of research is a quasi-experimental with non-equivalent control group design. The population was all students of class X MIA MAN 2 Central Lombok, amount to 47 students with a sampling technique using saturated sample techniques,hence the sample used in this study was class X MIA-1 as an experimental group of 24 students and class X MIA- 2 as a control group of 23 students. Before being treated, both samples were given a preliminary test to determine their initial abilities. Based on homogeneity test results, both samples have the same initial ability. In the final test, obtained an average score of mastery of concepts from the experimental class of 66 with the highest score of 85 and an average score of the control class of 55 with the highest score of 75. The research hypothesis was tested with the t-polled variance test with a significance level of 5%, and the results obtained t_count = 3.63, while t_table = 2.02. Based on these results, it means that t_count is greater than t_table, so Ho is rejected. Thus, the conclusion is the Predict-Observe-Explain (POE) learning model assisted by virtual simulations has an influence on the mastery of physics concepts in high school students.